The Association Between Body Mass Index and Physical Activity Among Elementary School Children at Suka Asih 02 Public Elementary School Ceger Bekasi Regency - Reshma Khairunisa; Zulfi Narrifa Putri; Previarsi Rahayu; Beatrix Elizabeth (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Nutritional status and physical activity are important indicators in assessing the health of elementary school–aged children. An imbalance between nutritional intake and physical activity may adversely affect children’s growth and development. A preliminary study conducted at Suka Asih 02 Public Elementary School, Ceger, Bekasi Regency, indicated a potential prevalence of undernutrition among some students, despite generally adequate levels of physical activity. This study aimed to analyze the association between Body Mass Index (BMI) and physical activity among elementary school children at Suka Asih 02 Public Elementary School. This study employed a quantitative observational analytic design with a cross-sectional approach. The sample consisted of 40 students from grades IV, V, and VI, selected using purposive sampling. Body Mass Index was measured using a calibrated weighing scale and stadiometer, while physical activity levels were assessed using PAQ-C. Data were analyzed using the Spearman Rank correlation test. The results showed that the majority of respondents (65.0%) were classified as underweight, whereas most respondents (82.5%) demonstrated good levels of physical activity. The Spearman Rank test revealed a statistically significant association between physical activity and BMI (p = 0.001; p < 0.05). The correlation coefficient (ρ = –0.496) indicated a moderate negative correlation between the two variables.